2015
DOI: 10.1126/sciadv.1501105
|View full text |Cite
|
Sign up to set email alerts
|

Defaunation affects carbon storage in tropical forests

Abstract: Populations of large frugivores are declining in tropical rainforests with potential consequences for carbon storage and climate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
358
1
22

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(393 citation statements)
references
References 98 publications
12
358
1
22
Order By: Relevance
“…The authors concluded that trees with seeds larger than 12 mm wide present high carbon storage capacity, and that large dispersers are functionally connected to the planet's climate regulation, given their distinct link with these trees. The study found a robust support for the hypothesis that the absence of large trees (larger in stature and harder wood) would affect carbon stocks in defaunated tropical rainforests (Bello et al 2015).…”
Section: Effects On the Provision Of Ecosystem Servicessupporting
confidence: 54%
See 1 more Smart Citation
“…The authors concluded that trees with seeds larger than 12 mm wide present high carbon storage capacity, and that large dispersers are functionally connected to the planet's climate regulation, given their distinct link with these trees. The study found a robust support for the hypothesis that the absence of large trees (larger in stature and harder wood) would affect carbon stocks in defaunated tropical rainforests (Bello et al 2015).…”
Section: Effects On the Provision Of Ecosystem Servicessupporting
confidence: 54%
“…Koerner et al (2016), for example, have shown a strong correlation between hunting intensity promoted by around 60 villages in northern Gabon and a defaunation gradient, evidenced by changes in diversity, relative abundance and composition of the mammal community. Because the various levels that make up an ecosystem are interdependent, changes in communities of hunted species Brazilian Atlantic Forest fragments (≥ minimum area 1000 ha) were analyzed, the important contribution of large tree seeds for the storage of atmospheric carbon was observed (Bello et al 2015). The authors concluded that trees with seeds larger than 12 mm wide present high carbon storage capacity, and that large dispersers are functionally connected to the planet's climate regulation, given their distinct link with these trees.…”
Section: Effects On the Provision Of Ecosystem Servicesmentioning
confidence: 99%
“…Conceptual frameworks predict that large-seeded species are mostly at risk from the negative impacts of defaunation owing to the extirpation of their large-bodied primary dispersers [23,24]. Here, we demonstrate that large seeds may also be differentially vulnerable to the loss of their secondary dispersers through anthropogenic driven reductions in large-bodied dung beetles [33,48].…”
Section: Resultsmentioning
confidence: 78%
“…We therefore have a poor understanding of direct effects of diversity within higher trophic levels or the indirect, cascading effects of biodiversity loss across tropic levels (but see [14]). There is mounting evidence that changes in forest vertebrate communities can lead to direct top-down consequences for plant demography, community composition and diversity [15][16][17][18][19][20][21][22], with knock-on effects for forest services and resilience [23,24]. However, because the indirect, multitrophic consequences of changing mammal communities are rarely experimentally tested, we have limited understanding of the ecosystem-wide consequences of anthropogenic impacts on tropical forests.…”
Section: Introductionmentioning
confidence: 99%
“…The main change is the increase in the abundance of plant species that have no dispersion associated with vertebrates, to the detriment of other species with large seeds that are dispersed by large vertebrates (Terborgh et al 2008, Culot et al 2017. Such a change in plant community caused by defaunation is detrimental to the carbon market, since large biomass trees can have their recruitment reduced by the absence of their dispersers, reducing the carbon stock of the areas (Bello et al 2015, Peres et al 2016 Acre is considered of extreme importance for the conservation of mammals. The State has approximately 86% of its territory covered by forests and is situated in one of the areas with the most endemic plants of the Amazon (Maury 2002, INPE 2016.…”
Section: Introductionmentioning
confidence: 99%